Internationalization of Medical Education—Concepts and Approaches for Action - Wu, Anette (International Higher Education, 2022)
The need for internationalization of medical education (IoME) is heightened amid the COVID-19 pandemic. IoME is the process of purposefully integrating international, intercultural, or global dimensions into medical education. Innovative and inclusive approaches are utilized in IoME in order to increase global healthcare collaboration and improve the health of all people worldwide.